Inclusive growth K N Raj's essays on economic development in the Economic Weekly and Economic and Political Weekly - Raj K N; Mody Ashoka (Mumbai Orient Longman, 2006)
The Essays in this book reflect Professor K.N. Rajts abiding interest in economic growth as a fundamental mechanical for lifting the poor and the disadvantaged. Raj was also concerned that the political bargaining process may end up undermining growth an
Keywords: Economic development; India